(untitled) (قضايا سياسية, 2023)
Building political and constitutional institutions and the performance of the political system in Iraq after 2003 The institution-building process is one of the basic ingredients for building a contemporary state with democratic features and political participation in accordance with an independent election law, meaning a state of institutions that adopts the law and the constitution, the separation of powers and an independent judiciary, which happened in Iraq after 2003. One of the most important foundations for building a state of institutions is the permanent constitution of the year2003. In addition, institutional building includes goals for change at all political, economic and social levels, in a way that supports the development of public policies and their effective and efficient implementation of performance and institutional work. Therefore, institution building is a means and an end.